ANALISIS EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PENGGAJIAN KARYAWAN PADA PT. KERISMAS WITIKCO MAKMUR FACTORY BITUNG - Vinastri, Maya Ariesti; Morasa, Jenny; Pangerapan, Sonny (JURNAL RISET AKUNTANSI GOING CONCERN, 2019)
The quality of human resources can be improved along with the implementation of the system implemented by the company. The payroll accounting system is a system that can handle and report transactions, as well as salary payment procedures for both monthly and daily performance. This study aims to determine the effectiveness of the payroll accounting system applied at PT. Kerismas Witikco Makmur. This type of research is descriptive qualitative by taking primary data directly through interviews with 10 respondents on the object of research. The results of the study show the payroll system applied by PT. Kerismas Witikco Makmur still uses a manual system and there has been a clear division of tasks within the company.Keywords: Effectiveness, Accounting Information Systems, Payroll, Employees